Parkinson disease patients' perspectives on palliative care needs: What are they telling us?. Issue 3 (June 2016) - Boersma, Isabel; Jones, Jacqueline; Carter, Julie; Bekelman, David; Miyasaki, Janis; Kutner, Jean; Kluger, Benzi
Abstract: Background: A growing body of literature suggests that patients with Parkinson disease (PD) have many unmet needs under current models of care that may be addressed through palliative care approaches. A first step in improving care for patients with PD through palliative care principles is to better understand patient perspectives on their perceived needs and care preferences. Methods: A total of 30 in-depth individual interviews and 4 focus groups were held to elicit the perspectives of patients with PD on unmet palliative care needs and preferences for addressing these needs. We used ATLAS.ti and inductive qualitative data analysis techniques to interpret responses. Results: Patients articulated major challenges in living with a diverse and complex set of motor and nonmotor symptoms; feelings of loss; changes in roles, relationships, and concept of self; and expressed concerns about the future. Participants discussed gaps in their care, including support at the time of diagnosis, education about the disease, and advance care planning. There was an expressed interest in and openness of participants to interdisciplinary approaches for addressing these needs. Conclusions: PD has a profound effect on multiple domains of a person's life starting at diagnosis. Patients desired individualized care and identified several areas where care from their primary neurologist could be improved. Patients were receptive to outpatient team-based palliative care services to address psychosocial issues, adjustment to illness (particularly at diagnosis and with progression), nonmotor symptom control, and advance care planning as an adjunct to usual care. Future research is needed to develop and test the effectiveness of palliative approaches to improve the care of patients with PD.